Peer-Tutor Assisted Problem-Based Learning Model on Mathematics Critical Thinking - Ximenes, Elsa Natalia; Suarjana, I Made; Wirabrata, Dewa Gede Firstia (MIMBAR PGSD Undiksha, 2023)
The mid-semester summative mathematics results stated that grade IV students needed remedial because the ability to solve problems was still low, indicating low critical thinking skills. Based on observations, this occurs because of the need for more interaction that activates students, and the learning process does not invite students to solve problems. The application of learning models affects the improvement of critical thinking skills and being able to activate learning. This study aimed to analyze the significant effect of the Peer Tutor assisted model on the Ability to Think Critical Mathematics in Grade IV Elementary School. This type of research used quasi-experimental (quasi-experimental) with a nonequivalent posttest-only control group design. The research population was ten groups of class IV elementary schools in Cluster IV. Determination of the sample using a random sampling technique with 2 groups, namely experimental and control. The data collection method is a description test method of 6 items. Data analysis was carried out descriptively and inferentially. This study's results are the experimental group's average posttest score, 90.20, and the average posttest score of the control group, 52.94. So, the average post-test score of the experimental group is greater than the control group. The results of the hypothesis show a significant effect of the peer tutor-assisted model on the critical thinking skills of students in grade IV elementary school. It was concluded that the peer tutor-assisted model significantly improves critical thinking skills in mathematics.